PERBANDINGAN NILAI SATURATION FLOW ANTARA METODE TIME SLICE DENGAN PENDEKATAN DPU 1997. (STUDI KASUS: PERSIMPANGAN JALAN KEBO IWA DENGAN JALAN ARTERI GATOT SUBROTO BARAT) - Widana Negara, Nyoman; Kwintaryana, Putu; Bandesa Wibawa, I Gede Arya Satria (JURNAL SPEKTRAN, 2019)
COMPARISON OF SATURATION FLOW VALUE BETWEEN THE TIME SLICE METHODS WITH THE DPU (1997) APPROACH. (CASE STUDY: INTERSECTION KEBO IWA STREET WITH WEST ARTERIAL ROAD GATOT SUBROTO) ABSTRACT Saturation flow is an important factor in the process of planning, designing and evaluating traffic light junctions. The purpose of this study is to find out protected saturation flow in traffic light junctions. Traffic volume data obtained from the Automatoc Traffic Control System (ATCS) recorded, and the number of residents obtained from the relevant agencies. While data such as geometric intersections, traffic signal aspects and side frictions were survey manually. The research design used is a comparative analysis between saturation flow measurements based on the Time Slice method and the DPU (1997) approach. In this study applied 2 (two) treatments, namely Treatment-1; measurement and analysis of saturation flow values based on lane width and Treatment-2; measurement and analysis of saturaton flow values based on total approach width. The results of the measurement and analysis in Treatment-1, obtained that the saturation flow value is very varied depending on the pattern of traffic movements. In the straight lane movement (S1-1), the value of saturation flow based on the Time Slice method obtained at 2.130 pcu / hour is greater than 10% compared to DPU (1997) of 1.976 pcu / hour. Meanwhile in the straight lane with the right turn movement (S1.2), the saturation flow value based on the Time Slice method of 1.681 pcu / hour is 13% smaller than DPU (1997) of 1,935 pcu / hour. Whereas, the results of measurement and analysis at Treatment-2; the saturation flow value is relatively the same, with the value of saturation flow respectively is based on the Time Slice method of 3.856 pcu / hour, DPU (1997) of 3,870 pcu / hour and the combined saturation flow at Treatment-1 is 3,811 pcu / hour .